Powerful Custom, Dominated Country: Domination of functionary Custom over Village Government in Kerinci - Maulana, Rio Yusri; Wahid, Makmun; Efendi, Dori; Rakhman, Moh. Arif; Yusuf, M.; Lega, Michael (Universitas Muhammadiyah Yogyakarta, 2021)
The discussion on the power relationship between the state and adat or customs is always exciting because althoughÂ adat is most likely getting tension from the state through various regulations, it keeps signifying its existence. An interesting phenomenon that happened after the downfall of the New Order regime and the expansion of the Regional Autonomy Systemâ€™s implementation was adat powerâ€™s reappearance at the local level. For instance, Adat Functionary in the Kerinci Regency signified their dominance over the village government. The studies about the relationship between adat and the state tend to put adat as an identity and spirit for gaining support, power, and fund also tools to deal with the government. This study begins with the fact that adat is dominant over the village government in decision-making. This study found in the Kerinci regency obtained a new government structure by the returning of adat power in governance, and affected the stability of the village administration, also used it as the solidarity mechanism of the community in Kerinci Regency to resolve various conflicts. Thus, the meaning of domination, which is commonly interpreted as something negative, is turning out to be a contrary one since it makes the community more solid through adat.